Hot-pressing process modeling for medium density fiberboard (MDF) - Norberto Nigro; Mario Storti (International Journal of Mathematics and Mathematical Sciences)
We present a numerical solution for the mathematical modeling of the hot-pressing process applied to medium density fiberboard. The model is based on the work of Humphrey (1982), Humphrey and Bolton (1989), and Carvalho and Costa (1998) with some modifications and extensions in order to take into account mainly the convective effects on the phase change term and also a conservative numerical treatment of the resulting system of partial differential equations.